Advamcement of Technology and ITS Impact on Modern Society - Maheswari, Diva Afirlia; Syakuru, Nazwa; Rahmadany, Loisha Adellia; Sulistiani, Heni (IC-ITECHS, 2024)
This study explores the rapid advancements in technology and their impact on modern society, focusing on sectors such as communication, healthcare, education, transportation, and entertainment. It examines the positive contributions of technological innovations while addressing challenges like cybersecurity threats, privacy concerns, and automation. The research employs qualitative analysis, integrating data from various academic sources. The findings reveal that technological advancements significantly improve efficiency and accessibility, but ethical considerations are crucial for sustainable progress.